Effect of isoverbascoside, a phenylpropanoid glycoside antioxidant, on proliferation and differentiation of human gastric cancer cell. - CHEN Rui-Chuan; SU Jin-Hua; YANG Shan-Min; LI Ji; WANG Tian-Jiao; ZHOU Hong (Acta Pharmacologica Sinica, 2016)
AIM: To investigate the effects of phenylpropanoid glycoside antioxidant isoverbascoside on cell proliferation and differentiation of human gastric cancer cell line MGC 803. METHODS: MGC 803 cells were treated with isoverbascoside. Its effects on cell proliferation, tumorigenicity, enzymatic activities, cell cycles, and gene expression were respectively evaluated with cell counting, tumor formation assay, enzymatic assay, flow cytometer analysis, and Western blotting, with Me2SO as positive control. RESULTS: Isoverbascoside could markedly inhibit cell proliferation in dose- and time-dependent manner. Isoverbascoside 20 micromol/L strikingly suppressed cell tumorigenicity, activities of alkaline phosphatase (ALP), and lactate dehydrogenase (LDH), and caused G0/G1 arrest. The expression of G1 S checkpoint related proteins, p53, p21/WAF1, and p16/INK4, were up-regulated after MGC 803 cells were treated with isoverbascoside 20 micromol/L for 4-8 h. Contrarily, the expression of C-myc protein was suppressed after 8 h treatment. CONCLUSION: Isoverbascoside inhibited cell proliferation, reversed cell malignant phenotypic characteristics, and consequently caused differentiation in MGC 803 cells. These effects might be associated with its activities of causing G0/G1 arrest and regulating the expression of cell cycle related proteins.